Is adult cardiac regeneration absent in Xenopus laevis yet present in Xenopus tropicalis? - Marshall, Lindsey; Girardot, Fabrice; Demeneix, Barbara A.; Coen, Laurent (Cell & bioscience, 2018)
We recently used an endoscopy-based resection method to explore the consequences of cardiac injury in adult , obtaining the result that the adult heart is unable to regenerate. At 11 months post-amputation, cellular and biological marks of scarring persisted. We thus concluded that, contrary to urodeles and teleosts, adult anurans share a cardiac injury outcome similar to adult mammals. However, in their work published in this journal on the 13 December 2017, Liao et al. showed that the adult heart is capable of efficient, almost scar free regeneration, a result at odds with our previous observation. These findings contrast with and challenge the outcome of adult heart repair following injury in species. Here we discuss the question of the intrinsic cardiac regenerative properties of an adult heart in anuran amphibians.